Կանխատեսման տեխնիկաների (գործիքներ) կիրառությունը քաղաքական որոշումներ ընդունելիս - Ստեփանյան, Նունուֆար (YSU Journal of International Affairs, 2014)
Policy making is the key of the political processes. In order to understand the policy of the state, first of all it is necessary to know how decisions are beingmade. As during decision making-policy the level of uncertainty is very high, so a number of methods have been developed, which are specific tools. In the framework of this article those forecasting techniques of political decision-making were classified (the Delphi technique, Scenario building, SWOT Analysis, Wild cards), which are more applicable to the decision-making policy in the legislative bodies. As a tool, these techniques may be used during a comprehensive analysis of decision-making policy. Totally, using above mentioned techniques, first of all solves the problem of uncertainty, and then the most important issue of political decision-making process: making effective and actual decision. Today in the political decision-making process only rational thought, intuition, theexperience are not enough for making effective decisions. The knowledge of forecasting techniques of political decision-making becomes more demanded.
Keywords: political decisions, forecasting techniques, decision - making policy, tools, the Delphi technique, Scenario building, SWOT Analysis, Wild cards, effect of groupthink, political frame